Students on the Frontlines of Academic Integrity in Ireland and Croatia: Who Are They and (Why) Do We Need Them? - Pavletić, Pegi; O’Connor, Megan (Journal of Academic Writing, 2025)
The standards and guidelines for quality assurance in the European Higher Education Area (ESG), define, within the standard 1.1, that higher education institutions (HEIs) need to have public internal Quality Assurance (QA) policies that effectively support academic integrity and are battling academic fraud, among other points (ENQA et al., 2015). On a national level (standard 3.6), QA agencies need to assure the integrity of their activities, in that way assuring that the national higher education (HE) systems are reliable, resilient and fit for purpose. When it comes to student involvement in QA, students are becoming increasingly engaged in QA activities as equal partners (ESU, 2020); however, the extent of their involvement in the matters of academic integrity on a national level still varies based on the national legislation and the activities covered by national QA agencies. Some countries, such as Ireland and Croatia, do involve students in discussions about academic integrity, prevention of academic misconduct, and implementation of different methods to preserve academic values within the curricula. In this paper, we have described the differences between the two mentioned national systems in terms of legislation, practices in preserving academic integrity within the Quality Assurance (QA) of higher education, and students’ reflections based on the information available at the webpages of the respective NUSs (Union of Students in Ireland and Croatian Students’ Council). In Ireland, the national QA Agency, Quality and Qualifications Ireland, has formed a National Academic Integrity Network (NAIN), and is directly involved in monitoring academic integrity practices and preventing academic misconduct, with the possibility of persecuting said misconduct. NAIN’s members include students who engage through their NUS - Union of Students in Ireland (USI), and who actively contribute to co-creation of policies and practices related to academic integrity. The student members receive appropriate training and are able to train and organise capacity-building activities for other students. The students also organise different activities on their own, to raise awareness on the need for battling academic misconduct such as contract cheating. In Croatia, the national QA Agency, Agency for Science and Higher Education (ASHE), is monitoring academic integrity through institutional self-assessment reports within internal QA evaluations, while the Law on Students’ Council and Other Students’ Organisations defines the position of students’ ombudspersons at each HEI, independently from the QA system. Students’ ombuds are students who do not receive training, but are able to request institutional reports. They are selected for a period of 1 year by the institutional students’ representation body, and they can help other students in protection of their rights in disciplinary processes. QQI and ASHE were interviewed as part of this research, and the findings indicate that QQI was much more successful in terms of engaging students in academic integrity-related topics, while ASHE does not have a responsibility to independently work on this topic with students, although they periodically participate in activities related to academic integrity. Students involved in QQI’s NAIN Network are independent and they understand the academic integrity policy well. Both the agencies reiterated the importance of students’ involvement in academic integrity and the need for educating students on these topics within their study cycles. Students who are overall most engaged in academic integrity are already active students’ representatives, which means that additional efforts need to be made in order to ensure all students understand this topic.